Symptoms of social anxiety, depression, and stress in parents of children with social anxiety disorder - Halldorsson, B; Draisey, J; Cooper, P; Creswell, C (Wiley, 2018)
It has been suggested that elevated maternal social anxiety may play a disorder-specific role in maintaining childhood social anxiety disorder (SAD), but few studies have examined whether mothers of children with SAD are more socially anxious than mothers of children with other anxiety disorders (ANX). This study set out to examine whether symptoms of social anxiety were more severe amongst mothers of 7-12 year old children presenting for treatment with SAD (n = 260) compared to those presenting with ANX (n = 138). In addition, we examined whether there were differences between these two groups in terms of maternal and paternal general anxiety, depression, and stress.Parents of 7-12 year old children referred for treatment of SAD or ANX completed self-report questionnaire measures of emotional symptoms.Compared to mothers of children with ANX, mothers of children with SAD reported significantly higher levels of social anxiety, general anxiety, and depression. In addition, fathers of children with SAD reported significantly higher levels of anxiety, stress, and depression than fathers of children with ANX.This study is one of the few existing studies that have examined mothers' and fathers' psychopathology across different childhood anxiety disorders. Compared to parents of children with ANX, parents of children with SAD may have poorer mental health which may inhibit optimum child treatment outcomes for children with SAD. Thus, targeting parental psychopathology may be particularly important in the treatment of childhood SAD.Consideration of parental psychopathology may be particularly important in the treatment of childhood social anxiety disorder. Mothers of children with social anxiety disorder are more socially anxious than mothers of children with other anxiety disorders Fathers of children with social anxiety disorder are more anxious and depressed than fathers of children with other anxiety disorders Participants were predominantly of high socioeconomic status. Parental diagnostic information was not obtained.